COMPARATIVE TYPOLOGY AS A BRANCH OF GENERAL LINGUISTICS (Modern education and development, 2025)
This article explores comparative typology as a branch of general linguistics, discussing its significance, research methods, results, and practical applications. By examining linguistic similarities and differences, comparative typology contributes to a deeper understanding of language universals, structural variations, and the cognitive foundations of human language.Ushbu maqolada qiyosiy tipologiya umumiy tilshunoslikning bir tarmog‘i sifatida o‘rganilib, uning ahamiyati, tadqiqot usullari, natijalari va amaliy qo‘llanilishi muhokama qilinadi. Qiyosiy tipologiya tildagi oʻxshashlik va farqlarni oʻrganib, til universalligi, strukturaviy oʻzgarishlar va inson tilining kognitiv asoslarini chuqurroq tushunishga yordam beradi.В данной статье рассматривается сравнительная типология как раздел общего языкознания, обсуждаются ее значение, методы исследования, результаты и практическое применение. Изучая лингвистические сходства и различия, сравнительная типология способствует более глубокому пониманию языковых универсалий, структурных вариаций и когнитивных основ человеческого языка.